Relationship of Age, Gender, and History of Comorbid Diseases in TB Patients toward Self-Stigma TB in Surakarta - Ignes Widowati; Balgis Balgis; Sri Mulyani (Faculty of Public Health Universitas Indonesia, 2021)
Tuberculosis (TB) infection in Indonesia has not been completely eradicated. It is challenging for those who suffer from TB to be away from self-stigma. This study aimed to determine the relationship between age factors, gender, and a history of comorbid diseases related to self-stigma. This was a cross sectional study using a Tuberculosis Stigma Assessment questionnaire. Total 50 respondents were obtained by purposive sampling technique. Inclusion criteria are TB patients or former patients aged 18 years to the elderly, male and female, without or having a history of comorbidities (HIV & DM). Quantitative-qualitative analysis, univariate and bivariate tests using Pearson Correlation and Chi Square were employed. Based on the Pearson correlation test there were no relationships between age and stigma, adolescent (p = 0.506), adult (p = 0.732), and elderly (p = 0.539),. Through Chi Square test, there was no relationship between the gender and stigma (p=0.520) . Likewise, a history of comorbid disease with TB stigma which p-value 0.537 did not show any relationship. Quantitatively, 78% of respondents were stigmatized, where respondents tend to be shy and not open about their TB status. There were 78% of respondents were stigmatized but no significant relationships between age, gender, and history of comorbid diseases on TB self-stigma